The Difussion Innovation Of Stunting Derivation Through Nona Helix Model - Amalia, Bella; Rakhma Fitriani, Dinda (International Journal of Educational Research & Social Sciences, 2024)
This article discussed the diffusion innovation process of government programs with development communication studies on the stunting reduction acceleration in Tangerang City. This research used a qualitative case study approach and a constructivist paradigm. The theory used is the diffusion innovation theory. The results of this research indicated that the diffusion innovation process occurred through the dissemination of information related to stunting reduction efforts to target community groups in Tangerang City with several communication channels, namely face-to-face communication or counseling, publication of activities through social media and mass media. This research produces a model, namely The Nona Helix of Benteng City.